Clinical influences on antibiotic prescribing decisions for lower respiratory tract infection: a nine country qualitative study of variation in care. Issue 3 (22nd May 2012) - Brookes-Howell, Lucy; Hood, Kerenza; Cooper, Lucy; Coenen, Samuel; Little, Paul; Verheij, Theo; Godycki-Cwirko, Maciek; Melbye, Hasse; Krawczyk, Jaroslaw; Borras-Santos, Alicia; Jakobsen, Kristin; Worby, Patricia; et al.
Abstract : Objectives: There is variation in antibiotic prescribing for lower respiratory tract infections (LRTI) in primary care that does not benefit patients. This study aims to investigate clinicians' accounts of clinical influences on antibiotic prescribing decisions for LRTI to better understand variation and identify opportunities for improvement. Design: Multi country qualitative interview study. Semi-structured interviews using open-ended questions and a patient scenario. Data were subjected to five-stage analytic framework approach (familiarisation, developing a thematic framework from the interview questions and emerging themes, indexing, charting and mapping to search for interpretations), with interviewers commenting on preliminary reports. Setting: Primary care. Participants: 80 primary care clinicians randomly selected from primary care research networks based in nine European cities. Results: Clinicians reported four main individual clinical factors that guided their antibiotic prescribing decision: auscultation, fever, discoloured sputum and breathlessness. These were considered alongside a general impression of the patient derived from building a picture of the illness course, using intuition and familiarity with the patient. Comorbidity and older age were considered main risk factors for poor outcomes. Clinical factors were similar across networks, apart from C reactive protein near patient testing in Tromsø. Clinicians developed ways to handle diagnostic and management uncertainty through their own clinical routines. Conclusions: Clinicians emphasised the importance of auscultation, fever, discoloured sputum and breathlessness, general impression of the illness course, familiarity with the patient, comorbidity, and age in informing their antibiotic prescribing decisions for LRTI. As some of these factors may be overemphasised given the evolving evidence base, greater standardisation of assessment and integration of findings may help reduce unhelpful variation in management. Non-clinical influences will also need to be addressed.